Interdisciplinary situational teaching for postgraduate connotative development: An integrated perspective of scaffolding theory and symbolic interactionism - Liang, Wenrui; Li, Jianhui; Wei, Jiang; Min, Yang; Lam, Ashura Tim Zoi (Journal of International Students, 2025)
As China’s higher education shifts toward connotative development, graduate education must prioritize quality enhancement and structural optimization. This study investigates how interdisciplinary courses foster connotative development by integrating scaffolding theory​and​symbolic interaction theory, examining their impact on cognitive growth and social interaction. Through semi-structured interviews with seven graduate students from Chinese-foreign cooperative programs, the research identifies key factors, teacher guidance, course design, and group collaboration that shape learning methods, knowledge transfer, and critical thinking. Findings reveal that guided teaching, social issue discussions, and experiential learning in interdisciplinary settings promote independent exploration and multidisciplinary perspectives, offering an innovative model for graduate education reform. The study provides theoretical insights and practical strategies to advance connotative development in China’s higher education system.